Large-Scale Plantlet Conversion and Ex Vitro Transplantation Efficiency of Siberian Ginseng by Bioreactor Culture. (31st October 2013) - Yang, Jingli; Zhao, Shicheng; Yu, Changyeon; Li, Chenghao
Abstract : To achieve large-scale low-cost ex vitro acclimatization of Siberian ginseng plants, heart- and torpedo-shaped secondary somatic embryos (SEs) induced from germinated SEs on agar medium were collected and then inoculated to 10-l bubble column bioreactor, respectively. For plantlet conversion, inoculation of torpedo-shaped secondary SEs was more effective than heart-shaped SEs. TS2 (culture of torpedo-shaped SEs in a bioreactor with a 2-week subculture interval) plantlets had a higher root number and leaf number and larger leaf area than did HS3 (culture of heart-shaped SEs in a bioreactor with a 3-week subculture interval) and HS2 (culture of heart-shaped SEs in a bioreactor with a 2-week subculture interval) plantlets. Of these converted plants, TS2 plantlets had higher survival rate (83.7%) and growth characteristics after transplantation in a simple shed covered with a 50% sunshade net only for 6 months. TS2 plantlets also showed significantly lower H2 O2 content and significantly increased superoxide dismutase ( SOD ), glutathione peroxidase ( GPX ), and glutathione transferase ( GST ) expression levels as compared to HS2 plants when exposure to ex vitro conditions.